2018
DOI: 10.5812/jjm.63131
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Determination of CTX-M1 Producing Klebsiella pneumoniae Using Multilocus Variable-Number Tandem Repeat Analysis, Semnan, Iran

Abstract: Background: CTX-M is the most prevalent and rapidly growing type of the extended-spectrum β-lactamase (ESBL) family and CTX-M1 is the most common type of blaCTX-M. Objectives: The current study aimed at investigating the genetic diversity of CTX-M-1-producing Klebsiella pneumoniae circulating in Semnan, Iran evaluated by multilocus variable-number tandem repeat analysis (MLVA). Methods: A total of 110 isolates of K. pneumoniae were collected from different clinical samples. The antibiotic suceptibility and dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…The results of two independent studies conducted by Saeed and Dadie indicated that most of the isolates belonged to group A, which is in contrast to our study [37,38]. This difference in the phylogroup distribution can be due to several factors such as genetic, dietary, health, environmental and geographic conditions of the host [39][40][41].…”
Section: Discussioncontrasting
confidence: 81%
“…The results of two independent studies conducted by Saeed and Dadie indicated that most of the isolates belonged to group A, which is in contrast to our study [37,38]. This difference in the phylogroup distribution can be due to several factors such as genetic, dietary, health, environmental and geographic conditions of the host [39][40][41].…”
Section: Discussioncontrasting
confidence: 81%
“…MDR was defined as acquired resistance to at least one agent in three or more antimicrobial categories. XDR was defined as bacterial isolates remain susceptible to only one or two antimicrobial categories [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%